2016
DOI: 10.14746/sllt.2016.6.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Higher education teachers’ attitudes towards English medium instruction: A three-country comparison

Abstract: We report on a small scale study carried out in Austria, Italy and Poland which investigated the attitudes of university teachers engaged in teaching their academic subject through the medium of English. The data consisted of 25 teacher interviews. We focused on the topics of internationalisation of universities, on policy and resourcing, and on the levels of English proficiency (theirs and those of their students) needed for effective English medium instruction (EMI). We also observed whether there were diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(126 citation statements)
references
References 24 publications
(30 reference statements)
8
98
0
3
Order By: Relevance
“…Indeed, apart from the large scale statistical surveys reported in the introduction, there is an “almost total absence of any comparative studies amongst institutions and/or amongst countries” (Macaro et al, : 64). This is beginning to change with a number of recent publications (Dafouz et al, ; Dearden & Macaro, ; Jenkins & Mauranen, ) offering more in‐depth comparisons between EMI settings, at a range of levels from classroom practices, to stakeholder perceptions, and management policy. However, given the current paucity of data, no firm conclusions on either overarching issues or the relationships between different local concerns can be drawn and further research is needed.…”
Section: Emi Multilingualism and Extended Language Policymentioning
confidence: 99%
“…Indeed, apart from the large scale statistical surveys reported in the introduction, there is an “almost total absence of any comparative studies amongst institutions and/or amongst countries” (Macaro et al, : 64). This is beginning to change with a number of recent publications (Dafouz et al, ; Dearden & Macaro, ; Jenkins & Mauranen, ) offering more in‐depth comparisons between EMI settings, at a range of levels from classroom practices, to stakeholder perceptions, and management policy. However, given the current paucity of data, no firm conclusions on either overarching issues or the relationships between different local concerns can be drawn and further research is needed.…”
Section: Emi Multilingualism and Extended Language Policymentioning
confidence: 99%
“…These SUSs will also be able to attend graduate programs abroad more efficiently and continue their higher studies since most of the graduate programs use EMI. Dearden & Macaro (2016) surveyed lecturers in Austria, Italy, and Poland and found that a frequently cited advantage of EMI in these countries is giving students the same opportunities to study abroad. Additionally, these students will have access to the most recent developments in their field and more learning resources.…”
Section: Introductionmentioning
confidence: 99%
“…However, although our findings suggest that EMI practitioners at our university seem to be willing to teach in English, and are ready to change many aspects of their teaching methods, they do not seem to be ready to make the deeper changes necessary to implement a CLIL methodology in tertiary education, L L's "enriched pedagogy" which is "its major achievement" according to Ball, Kelly & Clegg (2015, p. 4). Therefore, we have to agree with O'Dowd (2018) ("lecturers themselves often do not believe in or see this need for a methodological shift … to more student-centred approaches", p. 3) and Dearden and Macaro (2016) who detected a "distinct lack of awareness of a need to change pedagogy in order to help students … to cope with content delivered through a second language", although they found that instructors seem to be "relatively open to the need for a revised pedagogy" (p. 479). The implications of these findings seem to be far-reaching.…”
Section: Discussionmentioning
confidence: 64%